How to write a scientific paper - Ali Hussain, Reshak, Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2013)
Academic Lecture Series 2011 How to write a scientific paper presented by Prof. Dr Ali Hussain Reshak, organized by Unit Pembangunan Lestari Universiti Malaysia Perlis(UniMAP), Perlis, Malaysia.